Improving electrical properties of iPSC-cardiomyocytes by enhancing Cx43 expression. (July 2018) - Sottas, Valentin; Wahl, Carl-Mattheis; Trache, Mihnea C.; Bartolf-Kopp, Michael; Cambridge, Sidney; Hecker, Markus; Ullrich, Nina D.
Abstract: The therapeutic potential of induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) is limited by immature functional features including low impulse propagation and reduced cell excitability. Key players regulating electrical activity are voltage-gated Na + channels (Nav 1.5) and gap junctions built from connexin-43 (Cx43). Here we tested the hypothesis that enhanced Cx43 expression increases intercellular coupling and influences excitability by modulating Nav 1.5. Using transgenic approaches, Cx43 and Nav 1.5 localization and cell coupling were studied by confocal imaging. Nav 1.5 currents and action potentials (APs) were measured using the patch-clamp technique. Enhanced sarcolemmal Cx43 expression significantly improved intercellular coupling and accelerated dye transfer kinetics. Furthermore, Cx43 modulated Nav 1.5 function leading to significantly higher current and enhanced AP upstroke velocities, thereby improving electrical activity as measured by microelectrode arrays. These findings suggest a mechanistic link between cell coupling and excitability controlled by Cx43 expression in iPSC-CMs. Therefore, we propose Cx43 as novel molecular target for improving electrical properties of iPSC-CMs to match the functional properties of native myocytes. Highlights: Enhanced Cx43 expression leads to increased gap junction formation in iPSC-CMs. Spatio-temporal characteristics of signal propagation are significantly improved. Cx43 expression co-regulates Nav 1.5 ion channel function and myocyte excitability.